Development of Family Literacy Culture through Read Aloud: Literature Review - Fuzy Abawaini; Tina Hayati Dahlan; Yeni Rachmawati (Proceedings of International Conference on Psychological Studies (ICPSYCHE), 2022)
This article aims to analyze the development of family literacy culture through Read Aloud. The scope studied in this article discusses the role of the family in developing a family literacy culture, implementing the Read Aloud strategy, and supporting factors for developing a family literacy culture. The method used in this study is a literature review. Source are taken from Read Aloud books and relevant articles on the role of family and Read Aloud which were obtained from Google Scholar, Researchgate, and Sciencedirect. The results of this literature review found that the role of the family in the development of family literacy culture are; motivator, role models, mentors, friends and promoters to create literacy beliefs and behaviors in children. In addition, Read Aloud stage was also found. The type and selection of books, the frequency and duration of reading and family support are things that need to be considered in reading aloud. It was also found that allow children to actively involve in read aloud activities will accelerate the effectiveness. The benefit of this study is to provide an overview and perspective to parents about developing an effective family literacy culture.